On the Practical Interest of Discrete Inverse Pólya and Weibull-1 Models in Industrial Reliability Studies - Pasanisi, Alberto; Roero, Côme; Remy, Emmanuel; Bousquet, Nicolas (Quality and reliability engineering international, 2015)
Engineers often cope with the problem of assessing the lifetime of industrial components, on the basis of observed industrial feedback data. Usually, lifetime is modelled as a continuous random variable, for instance, exponentially or Weibull distributed. However, in some cases, the features of the piece of equipment under investigation rather suggest the use of discrete probabilistic models. This happens for equipment that only operates on cycles or on demand. In these cases, the lifetime is rather measured in number of cycles or number of solicitations before failure; therefore, in theory, discrete models should be more appropriate. This article aims at bringing some light to the practical interest of the reliability engineer in using two discrete models among the most popular: the inverse Pólya distribution (IPD), based on a Pólya urn scheme, and the so‐called Weibull‐1 model. It is shown that for different reasons, the practical use of both models should be restricted to specific industrial situations. In particular, when nothing is a priori known over the nature of ageing and/or data are heavily right censored, they can remain of limited interest with respect to more flexible continuous lifetime models such as the usual (continuous) Weibull distribution. Nonetheless, the intuitive meaning given to the IPD could favour its use by engineers in low (decelerated) ageing situations. Copyright © 2015 John Wiley & Sons, Ltd.